Model study on bioremediation process for the treatment of polluted river through effective microorganisms. (2022) - Vijayanand, P.S.; Viswanathan, G.; Manjunath, N.V.; Balakrishnaraja, R.; Dharchana, R.; Ragashravanthi, R.
Abstract: The problem of fresh water deficiency is of worldwide impact. The increased population in addition to various human activities has led to a drastic and continuous shortage of freshwater resources. This leads to urge the scientific community to find radical and cheap solutions. Enzyme Microorganisms (EMs) are very effective in different types of waste water treatment process. Inoculants of EMs from Bannari Amman Sugars Industries, Bannari Amman Group (BAG), Sathyamangalam and Bint Biotech Pvt. (BINT), New Delhi are used for this present study to treat the polluted water from Noyyal river. The results indicated that the microbial agents play an important role in reducing the chemical oxygen demand (COD) and biochemical oxygen demand (BOD). The microorganisms present in the inoculants of BAG and BINT are highly effective in the treatment of waste water with high load of organic pollutants. Further the treated water analysis indicates the quality meets for agricultural utility.